Al-Āyāt Al-Qur’āniyyah ‘Alā Ḍau’ ‘Ilm Al-Aṣwāt Wa Aṡaruha Fi Al-Ma’nā - Achmad Khusnul Khitam (Pusat Studi Kependidikan (PSKp) Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an, 2020)
This paper deals with a very specific problem in term of the relationship between sound and its meaning in the Qur’an. As a scripture revealed with Arabic language as its medium, the Qur’an often uses some words or sentences that have an intimate relation between its meaning and the way of its expression. It means that the sounds which construct those words or sentences have a huge rule to determine meaning, and therefore, a single word or sentence which is expressed by using different voices may produce different meaning. This paper shows that the Qur’an has a very intimate relation between sounds which construct words or sentences and their meaning. It covers some parts of segmental and suprasegmental phonemes discussion in linguistics tradition, including the preference of phonemes, intonation, stress, juncture and so on. This research based on library research, a research proceed by gathering some facts from various books, articles, and other literatures related to the subject. This research combines semantic and phonological approach with analytic description method. From this research, it is found that the words or sentences of the Qur’an have some ways to express its voices or phonemes which construct words and sentences in order to show certain meaning. It means that some words or sentences of the Qur’an produce certain meaning based on the preference of its phonemes or voices.